Complexity and Choice: Reassessing Support for Women in Leadership Programs - Groombridge, Barbara; Worden, Suzette (Australian Technology Network Women's Executive Development (ATN WEXDEV), 2006)
Advice and support for achieving promotion is often one of the main tasks of leadership programs aimed at women in higher education. This paper will consider how leadership development strategies can be extended to meet current developments in higher education, where there is a need to respond to increasing complexity within the system, resulting from changes in government policy and the impact of globalisation.We propose that there is a need to address diversity in leadership roles to meet the challenge of complexity, as one outcome of a focus on promotion in leadership programs has been to emphasise and reinforce conventional managerial, hierarchical expectations of leadership. In this context, leadership is predominantly role-related and positional in nature. The ability to develop and change circumstances is gained through the power given by the role. Women in these roles are most often seen as successful leaders when they additionally demonstrate a nurturing and supportive approach.The paper will address the limitations of adopting this view of leadership and examine how leadership can be broadened by and for women in higher education. The paper will consider how different models of leadership in teaching and in research can be developed, and then their potential to influence broader leadership programs in higher education management.